A continued role for signaling functions in the early evolution of feathers. (1st March 2017) - Ruxton, Graeme D.; Persons IV, W. Scott; Currie, Philip J.
Abstract: Persons and Currie (2015) argued against either flight, thermoregulation, or signaling as a functional benefit driving the earliest evolution of feathers; rather, they favored simple feathers having an initial tactile sensory function, which changed to a thermoregulatory function as density increased. Here, we explore the relative merits of early simple feathers that may have originated as tactile sensors progressing instead toward a signaling, rather than (or in addition to) a thermoregulatory function. We suggest that signaling could act in concert with a sensory function more naturally than could thermoregulation. As such, the dismissal of a possible signaling function and the presumption that an initial sensory function led directly to a thermoregulatory function (implicit in the title "bristles before down") are premature.